Proof of Newton's Gravitation Law

The Planets revolving arround the sun forms an ellipse (1st kepler's law). Let the polar equation of the ellipse be \(r=\dfrac{l}{1+e\cos\theta}\).

Important thing to note that is we are assuming sun as the origin of the sysytem.

Let s\vec{s} be the position vector of the planet. s=l1+ecosθ(i^cosθ+j^sinθ)\Rightarrow \vec{s}=\dfrac{l}{1+e\cos\theta}(\hat{i}\cos\theta+\hat{j}\sin\theta) where θ\theta is the angle of s\vec{s} on the xaxisx-axis

Now let dAdA represent the area swept by the planet in time dtdt dAdt=k=constant From Keplers 2nd law\Rightarrow \dfrac{dA}{dt}=k=constant\space\blue{From\space Kepler's \space 2_{nd}\space law} dt=dAk\Rightarrow dt=\dfrac{dA}{k} Also dA=12r2dθAlso\space {dA}=\dfrac{1}{2}r^2{d\theta} dt=r2dθ2k=l2dθ2(1+ecosθ)2k\Rightarrow dt=\dfrac{r^2d\theta}{2k}=\dfrac{l^2d\theta}{2(1+e\cos\theta)^2k} v=dsdt=2(1+ecosθ)2kdsl2dθ\Rightarrow\vec{v}=\dfrac{d\vec{s}}{dt}=\dfrac{2(1+e\cos\theta)^2k\red{d\vec{s}}}{l^2\red{d\theta}} =2(1+ecosθ)2kl2(lesinθ(1+ecosθ)2(i^cosθ+j^sinθ)lesinθ1+ecosθ(i^sinθ+j^cosθ))=\dfrac{2(1+e\cos\theta)^2k}{l^2}\left( \dfrac{le\sin\theta}{(1+e\cos\theta)^2}(\hat{i}\cos\theta+\hat{j}\sin\theta) \dfrac{le\sin\theta}{1+e\cos\theta}(-\hat{i}\sin\theta+\hat{j}\cos\theta) \right) =2kesinθl(i^cosθ+j^sinθ)+2k(1+ecosθ)l(i^sinθ+j^cosθ)=\dfrac{2ke\sin\theta}{l}(\hat{i}\cos\theta+\hat{j}\sin\theta)+\dfrac{2k(1+e\cos\theta)}{l}(-\hat{i}\sin\theta+\hat{j}\cos\theta) =2kesinθcosθi^l2k(1+ecosθ)sinθi^l+2kesin2θj^l+2k(1+ecosθ)cosθj^l=\dfrac{2ke\sin\theta\cos\theta\hat{i}}{l}-\dfrac{2k(1+e\cos\theta)\sin\theta\hat{i}}{l}+\dfrac{2ke\sin^2\theta\hat{j}}{l}+\dfrac{2k(1+e\cos\theta)\cos\theta\hat{j}}{l} =2ki^l(esinθcosθsinθesinθcosθ)+2kj^l(esin2θ+cosθ+ecos2θ)=\dfrac{2k\hat{i}}{l}(e\sin\theta\cos\theta-\sin\theta-e\sin\theta\cos\theta)+\dfrac{2k\hat{j}}{l}(e\sin^2\theta+\cos\theta+e\cos^2\theta) =2kl(i^sinθ+j^(e+cosθ))=\dfrac{2k}{l}(-\hat{i}\sin\theta+\hat{j}(e+\cos\theta)) a=dvdt=dvdθ×2(1+ecosθ)2kl2\Rightarrow \vec{a}=\dfrac{d\vec{v}}{dt}=\dfrac{d\vec{v}}{d\theta}\times\dfrac{2(1+e\cos\theta)^2k}{l^2} =2kl×d(i^sinθ+j^e+j^cosθ)dθ×2(1+ecosθ)2kl2=\dfrac{2k}{l}\times\dfrac{d(-\hat{i}\sin\theta+\hat{j}e+\hat{j}\cos\theta)}{d\theta}\times\dfrac{2(1+e\cos\theta)^2k}{l^2} =4k2(1+ecosθ)2l3(i^cosθ+j^sinθ)=-\dfrac{4k^2(1+e\cos\theta)^2}{l^3}(\hat{i}\cos\theta+\hat{j}\sin\theta) Comparing this with rr a=4k2lr2(i^cosθ+j^sinθ)\Rightarrow \vec{a} =-\dfrac{4k^2}{lr^2}(\hat{i}\cos\theta+\hat{j}\sin\theta) a=4k2lr2\Rightarrow |\vec{a}|=\dfrac{4k^2}{lr^2} Now, if p,qp,q are semi-major and semi-minor axes of the ellipse and TT is the time period of the revolution k=πpqT,l=q2p\Rightarrow k=\dfrac{\pi pq}{T},l=\dfrac{q^2}{p} Also from 3rd law of Kepler T2=cp3, c is a constant for all planetsT^2=cp^3,\space\blue{c\space is\space a \space constant\space for\space all\space planets} a=4π2p3q2cp3q2r2=4π2cr2\Rightarrow |\vec{a}|=\dfrac{4\pi^2\cancel{p^3q^2}}{c\cancel{p^3q^2}r^2}=\dfrac{4\pi^2}{cr^2} a1r2\Rightarrow \boxed{|\vec{a}|\propto\dfrac{1}{r^2}}

Note by Zakir Husain
3 months, 2 weeks ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

There are no comments in this discussion.

×

Problem Loading...

Note Loading...

Set Loading...